Growth hormone treatment and left ventricular dimensions in Turner syndrome - Matura, Lea Ann (2007)
OBJECTIVE: To determine if cardiac dimensions were different in girls with Turner syndrome (TS) that did receive growth hormone (GH) vs. those who did not receive GH. STUDY DESIGN: This was a retrospective, cross sectional study analyzing echocardiograms in 86 females with TS divided into GH-treated (n=67) vs. untreated (n=19) groups. These were subjects with TS participating in the National Institutes of Health protocol between 2001 and 2006. RESULTS: The average age was 16.2 years (range 10-25 yrs) and duration of GH treatment was 4.4 (range 1-14 yrs). The GH-treated group was taller by ∼6 cm (P=0.004) but, cardiac dimensions normalized to body surface area (BSA), including septal and posterior wall thicknesses, left ventricular (LV) mass and LV internal diameters, were not significantly different in the two groups. The fractional shortening index was similar in the two groups. Multiple regression analyses indicated that BSA, but not duration of GH treatment predicted LV dimensions in girls with TS. CONCLUSIONS: GH treatment of girls with TS increases stature but does not disproportionately affect cardiac dimensions.